Labour-market reforms in Southern Europe: From protection to flexibility - Asensio, M.; Ferreira, C. (Economic recessions: Navigating economies in a volatile world and the path for economic resilience and development, 2024)
The study delves into the post-Eurozone crisis transformations within the labor market of Southern Europe, emphasizing the shift from a protective model to one characterized by increased flexibility. Notable alterations in labor regulation systems, including a decline in union density, heightened labor market deregulation, rising unemployment rates, and the proliferation of atypical and precarious employment forms, are underscored by the authors. The analysis extensively compares labor reforms across Greece, Italy, Portugal, and Spain emphasizing divergences in policies and their consequential economic and social impacts. Contrary to the conventional belief associating state intervention with market rigidity, the paper posits that robust government regulations can expedite wage adjustments and enhance overall work flexibility. The exploration of disparities between countries, rooted in preexisting levels of state intervention in their labor markets, further enriches the discussion. Ultimately, the study contends that responses to economic challenges, such as recessions and high unemployment, manifest in wage moderation and flexible working arrangements. These responses are intricately linked to economic contexts, encompassing factors such as inflation rates, productivity levels, and trade imbalances.